(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to fill a knowledge and practical gap by examining the impact of using relationship marketing dimensions (such as trust, commitment, communication, customer satisfaction, and interaction) on achieving a competitive advantage for telecommunications companies in the Kingdom, based on a solid theoretical and field framework. The study also seeks to provide applicable recommendations for improving relationship marketing strategies in this vital sector. The study recommends enhancing the dimensions of relationship marketing, particularly "trust," "customer satisfaction," and "commitment," given their direct impact on improving companies’ competitive performance. The study also recommends designing professional development programs that take into account employee needs based on years of experience and age, which will contribute to maximizing performance and increasing engagement with relationship marketing strategies.